122k views
4 votes
Solve y''+2y' - 3y = 0, y(0) = 3, y'(0) = 11 Preview y(t) = |2e^(-3t)+5e^t Points possible: 1 This is attempt 3 of 3 Score on last attempt: 0. Score in gradebook: 0 License Submit

User Bilbohhh
by
4.4k points

1 Answer

1 vote


y''+2y'-3y=0

Second order linear homogeneous differential equation with constant coefficients, ODE has a form of,


ay''+by'+cy=0

From here we assume that for any equation of that form has a solution of the form,
e^(yt)

Now the equation looks like this,


((e^(yt)))''+2((e^(yt)))'-3e^(yt)=0

Now simplify to,


e^(yt)(y^2+2y-3)=0

You can solve the simplified equation using quadratic equation since,


e^(yt)(y^2+2y-3)=0\Longleftrightarrow y^2+2y-3=0

Using the QE we result with,


\underline{y_1=1}, \underline{y_2=-3}

So,

For two real roots
y_1\\eq y_2 the general solution takes the form of,


y=c_1e^(y_1t)+c_2e^(y_2t)

Or simply,


\boxed{y=c_1e^t+c_2e^(-3t)}

Hope this helps.

r3t40

User Albattran
by
4.6k points